EVALUASI KUALITAS PELAYANAN PROGRAM PAMSIMAS DALAM MENINGKATKAN AKSES AIR BERSIH DI DAERAH PEDESAAN - Rusmawati, Rusmawati; Dompak, Timbul (Jurnal Progress Administrasi Publik, 2025)
The Community-Based Water and Sanitation Program (PAMSIMAS) plays an important role in improving the quality of life of rural communities by increasing access to clean drinking water and adequate sanitation facilities. This study aims to evaluate the impact of the program on community health, identify challenges in sustainable management, and provide recommendations for optimizing program implementation. The research method involves secondary data analysis and participatory surveys, involving beneficiary communities as the main respondents. The results of the study showed a significant increase in access to clean water, a decrease in the incidence of water-borne diseases, and the adoption of better hygiene practices. In addition, the program has succeeded in increasing community participation, thereby fostering a sense of ownership and responsibility for the infrastructure built. However, this study also identified a number of challenges that affect the sustainability of the program, including limited human resources and funding, and lack of adequate training and technical assistance for infrastructure management. To overcome these challenges, this study recommends the need for ongoing support in the form of training, resource allocation, and strengthening community institutional capacity. Overall, the conclusion that can be drawn is that PAMSIMAS has provided significant social, economic, and health benefits, and is an effective model for community-based water and sanitation management. These findings provide important contributions to the formulation of policies that support sustainable development goals in Indonesia.   Keywords: Evaluation; PAMSIMAS; Quality; Service